META ANALISIS MODEL BLENDED LEARNING MENGGUNAKAN PROBLEM-BASED LEARNING PADA PEMBELAJARAN BIOLOGI DI SMA(META-ANALYSIS OF THE BLENDED LEARNING MODEL IMPLEMENTING PROBLEM-BASED LEARNING IN BIOLOGY INSTRUCTION IN SENIOR HIGH SCHOOLS) - Faris, Sabrina; Suryani, Santi; Safitri, Dini; Ristanto, Rizhal Hendi (Jurnal Edukasi Biologi, 2025)
This study aims to analyze the application of the Blended learning model based on Problem-based Learning (PBL) in Biology learning at the high school level through the meta-analysis method. The research stages used are (1) identifying the type of research and the variables used, (2) recording the average value and standard deviation of the experimental and control groups, and (3) calculating the effect size using the unstandardized mean difference (UMD). Data were obtained from three studies relevant to this topic. The results of the analysis show that the PBL model based on blended learning significantly affects student learning outcomes, especially in improving critical thinking skills, scientific literacy, and problem-solving abilities. This approach involves PBL stages such as problem orientation, independent and group investigations, and reflection, effectively encouraging students to be more active, collaborative, and independent in learning. Overall, this study confirms that combining PBL with blended learning can support more innovative and effective biology learning at the high school level. The results of this study can be used as a reference by teachers to implement PBL learning using blended learning techniques.